Interakcije med mehurčki v milnični peni - Brumec, Gregor (Matrika, 2020)
Foam is a dispersion of gas bubbles in a liquid. In this article, the applications of foams and their main physical properties are presented. Deformation of a bubble under the action of a point force is discussed and the Morse-Witten theory is introduced. Deformation of the bubble under the action of multiple forces is calculated by minimizing the energy and compared with the predictions of the Morse-Witten theory. Finally, real foams are discussed and a few alternative models of the interaction between bubbles are presented.
Keywords: fizika mehke snovi; foam; pene; soft matter physics